An action research on using stories and drama in teaching English to primary students at Quan Tru Primary School - Vũ, Thị Thanh Tâm (University of Languages and International Studies, 2017)
It has been widely acknowledged that speaking and listening competence is an essential part of language learning. However, to the best knowledge of the researcher, Vietnamese EFL young learners do not have high competence of English speaking and listening.